Hydrogels for Modified-release Drug Delivery Systems - Zielińska, Aleksandra; Eder, Piotr; Rannier, Lucas; Cardoso, Juliana C.; Severino, Patrícia; Silva, Amélia M.; Souto, Eliana B. (Current Pharmaceutical Design, 2022)
Hydrogels for the modified-release drug delivery systems are a continuously growing area of interest for the pharmaceutical industry. According to the global market, the profit resulting from the use of polymers in this area is projected to reach 31.4 million by 2027. This review discusses the recent advances in and perspectives of hydrogel in drug delivery systems for oral, parenteral, nasal, topical, and ophthalmic delivery. The search was conducted, in January 2021, in an extensive database to identify studies published from January 2010 to December 2020. We described the main characteristic of the polymers to obtain an ideal hydrogel for a specific route of administration and the formulations. It was concluded that the hydrogels are useful to decrease the number of doses and side effects, promote adhesion of patient, and enhance the bioavailability of the drugs, thus improving the safety and efficacy of the treatment.
Keywords: drug delivery